AlimenTI: Um DApp de Suporte a Doação de Alimentos - Souza, Lidia Dias de; Silva, Fábio Santos da (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This work presents AlimenTI, a blockchain-based system designed to manage food donations. The goal is to enhance transparency, security, and traceability throughout the donation process. By leveraging smart contracts on the Ethereum network, every stage, from the registration of donations by supermarkets to the delivery to communities, is immutably recorded. The solution has the potential to reduce food waste, strengthen trust among stakeholders, and provide a scalable alternative for the efficient redistribution of food resources.